TOC, CN, and δ13C results of bulk organic matter in permafrost from the Lena Delta, Arctic - Tsai-Wen Lin; Tommaso Tesi; Alessio Nogarotto; Gesine Mollenhauer (PANGAEA, 2025)
This datasheet includes TOC, C/N, and δ13C results of bulk organic matter from permafrost collected from the Lena Delta. Samples were freeze-dried, homogenized, weighed ~15 mg into silver boats, acidified with 1.5 M HCl, and dried at 55 C. The analyses were conducted using a Thermo Fisher Scientific DeltaQ IRMS coupled with a FLASH 2000 CHNS Analyzer via a CONFLO IV gas mixing system at CNR-ISP in Bologna, Italy.
In: Lin, Tsai-Wen; Nehrke, Gernot; Mollenhauer, Gesine (2025): Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984732